Effect of Helicobacter Pylori Eradication on Human Gastric Microbiota: A Systematic Review and Meta-Analysis - Guo, Yang; Cao, Xue-Shan; Guo, Guan-Yi; Zhou, Meng-Ge; Yu, Bo (Frontiers in Cellular and Infection Microbiology, 2022)
Background: Helicobacter pylori (H. pylori) infection is a major risk factor for gastric cancer and eradication of H. pylori is recommended as an effective gastric cancer prevention strategy. The infected individuals show microbial dysbiosis of gastric microbiota. Accumulating studies have focused on gastric microbiota changes following H. pylori eradication in recent years. In the present study, we aim to evaluate the influence of successful H. pylori eradication on the short-term and long-term alterations of human gastric microbiota using a method of systematic review and meta-analysis. Methods: We did a systematic search based on three databases (PubMed, EMBASE, and Web of Science) in November 2021. Additional articles were also identified by reviewing references cited in the included papers. Human studies that reported changes of gastric microbiota following successful H. pylori eradication were enrolled. PROSPERO registration number: CRD42021293796. Results: In total, 9 studies enrolling 546 participants were included. Regarding quadruple therapy, alpha diversity indexes increased within one month after eradication; significant differences in gastric microbial community structure between before and after eradication were also seen within one month. The trends of above-mentioned diversity changes persisted with follow-up of six months. The microbial composition altered significantly after eradication and the relative abundance of H. pylori-related taxa decreased. Accordingly, gastric commonly dominant commensals enriched. Bioinformatic analyses of microbiota functions showed that bacteria reproduction related pathways down-regulated; pathways of gastric acid secretion etc. up-regulated. For triple therapy, similar trends of alpha diversity and beta diversity change were observed in the short-term and long-term follow-up. Also, after eradication, H. pylori was not the gastric dominant bacteria and similar changes of gastric microbial composition were found. For gastric microbial interactions, decrease of microbial interactions were seen after eradication. Additionally, regarding whether successful H. pylori eradication could restore gastric microbiota to uninfected status, the results remained controversial. Conclusion: In conclusion, successful H. pylori eradication could reverse the gastric microbiota dysbiosis and showed beneficial effects on gastric microbiota. Our findings may provide new insight for exploring the role of H. pylori and the whole gastric microbiota in gastric carcinogenesis.